SUPORT SYSTEM DECISION (DSS) PRESMA ELECTIONS OF UNIKI USING SIMPLE ADDITIVE WEIGHTHING METHODE (SAW) - Nunsina, Nunsina; Fadhilah, Cut; Kulbahri, Kulbahri (Universitas Dharmawangsa Medan, 2022)
ABSTRACTÂ Since minister lukman (2014-2019) and judge saifuddin (2014-2019) presented the discourse on religious censorship, the ministry of religions has continued to develop knowledge and strengthen religious censorship narratives through various digital platforms. The study focuses on the Ministry of the Republic of Indonesia's increased religious censorship on YouTube, the most popular social media platform for today's Internet users. The study draws several conclusions by combining a content analysis method with a descriptive analysis method. First, the intensity with which the YouTube channel is used to strengthen religious censorship issues needs to be increased. Only 15 (4.71%) of the 318 videos uploaded to the ministry of religion's YouTube account contain content on censorship and religious harmony. The annual frequency remained low, and there was no content on moderation and religious harmony in 2019. Second, religious censorship is still applied primarily to intellectuals who have not reached out to millennials. Its progress in eradicating negative issues related to the government's religious regulation program remains limited. Third, reaction data on censored and harmonized video content remains low, according to warganet. According to research, netizens prefer the term harmony to moderation. This suggests that the Indonesian people prefer harmony in general, but there are still some interpretations or negative impressions of the term